Causal relations between knowledge-intensive business services and regional employment growth - Thomas Brenner; Marco Capasso; Matthias Duschl; Koen Frenken; Tania Treibich (Philipps-University Marburg, Department of Geography, 2015)
This paper studies the causal relations between regional employment growth in Knowledge- Intensive Business Services (KIBS) and overall regional employment growth using German labour-market data for the period 1999-2012. Adopting a recently developed technique, we are able to estimate a structural vector autoregressive model in which the causal directions between KIBS and other sectors are examined including various time lags. One main finding holds that although regional growth has a negative short-term effect on KIBS, KIBS growth has a long-term positive effect on the whole regional economy. This result confirms the claim that KIBS can play a key role in regional policies. Distinguishing between financial and nonfinancial KIBS, we find that financial KIBS have a procyclical effect on regional growth underlining the potential de-stabilizing effect of a large financial sector.
Keywords: C53; O33; R10; 330; Employment growth; growth spillovers; KIBS; industrial dynamics; financial geography